Pengaruh Kekayaan Daerah, Jenis Pemerintahan, Dan Kualitas Audit Terhadap Pengungkapan Internet-Based Financial Reporting - Sari Kurniati; Purnama Siddi (INVENTORY: JURNAL AKUNTANSI, 2020)
This study aims to get empirical evidence related to the effect of wealth, complexity, local government type, and audit quality on the disclosure of internet-based financial reporting (IBFR) local governments in Java. The population is all local government districts/cities in Java in 2018. The sample was selected using purposive sampling method and obtained 102 local governments consisting of 26 local governments that publish their financial reports through its website and 76 local governments do not publish reports finance through the website. The method of analysis used in the study is the logistic regression. The results of this study indicate that the wealth of local government, the complexity of local government, local government types, and quality audits increase the likelihood of disclosure IBFR.Keyword: local government, wealth of local government, the complexity of local government, local government types, quality audits, and internet-based financial reporting.